Deming’s Quality Assurance System Model and Its Aplication in Education - Nikmah, Laily Faridhatun; As’aril Muhajir; Agus Zaenul Fitri (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The purpose of the study was to determine the Deming quality assurance system model and its application in education. This study uses a library research type. Literature research as a research conducted by reviewing various journals and related reference books. The results of the study indicate that the quality assurance system model according to Deming emphasizes the importance of customer satisfaction and continuous improvement through 14 famous points. Deming also stated that the majority of production failures are caused by managers, so improving the quality of managers is the key to improving overall quality. The PDCA ( Plan, Do, Check, Action ) management function developed by Deming is the basis for managing continuous quality improvement and is the basis for the development of Total Quality Management (TQM).